COMMON FACTORS AFFECTING GRADE-12 STUDENTS’ SPEAKING FLUENCY: A SURVEY OF CAMBODIAN HIGH SCHOOL STUDENTS - Thon Houn; Sereyrath Em (Jurnal As-Salam, 2022)
The current study aimed to investigate the common factors affecting speaking fluency of grade 12 English-language students studying in the upper secondary school. The participants were composed of 100 students studying in grade 12 and 10 government teachers of English, teaching in grade 12. In collecting the data, two different groups of participants were asked to fill in two different questionnaires with close-ended questions. The obtained data were quantitatively analysed with SPSS, and descriptive statistics were used to determine the number and percentage of the respondents. As a result, the study discovered that instructional methods and the fear of speaking caused by inhibition and anxiety strongly affected the students’ English-speaking fluency the most, as well as many other subsequent factors. Thus, this study can be useful for teachers of English to reconsider their weaknesses and strengths, to identify their weakness and strength in teaching speaking and ascertain the students’ deficiency and potency in learning to improve their English learning, specifically, speaking skills. The study could also be used to help the teachers better understand their students’ speaking difficulties, and find appropriate ways to teach them efficiently.